Age differences in patterns and confidence of using internet and social media for cancer-care among cancer survivors. Issue 6 (July 2020) - Eng, Lawson; Bender, Jackie; Hueniken, Katrina; Kassirian, Shayan; Mitchell, Laura; Aggarwal, Reenika; Paulo, Chelsea; Smith, Elliot C.; Geist, Ilana; Balaratnam, Karmugi; Magony, Alexander; Liang, Mindy; et al.
Abstract: Objectives: The internet and social media provide information and support to cancer survivors, and adolescent and young adults (AYA, age < 40 years), adults, and older (age 65+ years) cancer survivors may have different needs. We evaluated the impact of age on cancer-related internet and social media use and confidence in evaluating online information for cancer-care decision making. Materials and Methods: Cancer survivors completed a convenience cross-sectional survey evaluating their cancer-related internet and social media use and their confidence in using these resources for decision making. Multivariable regression models evaluated the impact of age on usage patterns and confidence. Results: Among 371 cancer survivors, 58 were older adults and 138 were AYA; 74% used the internet and 39% social media for cancer care; 48% felt confident in using online information for cancer-care decisions. Compared to adult survivors, there was a non-significant trend for older survivors to be less likely to use the internet for cancer-care information(aOR = 0.49, 95% CI[0.23–1.03], P = .06), while AYA were more likely to use social media for cancer-care (aOR = 1.79[1.08–2.99], P = .03). Although confidence at using online information for cancer-care decision making did not differ between age groups, increasing age had a non-significant trend towards reduced confidence (aOR = 0.99 per year [0.97–1.00], P = .09). Most commonly researched and desired online information were causes/risk factors/symptoms, treatment options, and prognosis/outcomes. Conclusions: Age may influence the use of internet and social media for cancer-care, and older cancer survivors may be less confident at evaluating online information for cancer-care decision making. Future research should explore other strategies at meeting the informational needs of older cancer survivors.